Identificación y análisis de los factores que aumentan el riesgo de toxicidad sistémica asociada al uso de anestésicos locales. - Merino Achance, Jennifer Alexandra (2025)
Local anesthetics (LAs) are widely used drugs in medical practice to reversibly block the conduction of nerve impulses, allowing surgical procedures and the control of postoperative pain. However, their use is not without risk, with local anesthetic systemic toxicity (LAST) being one of the most serious complications. This adverse reaction can occur with any local anesthetic and through various routes of administration, primarily affecting the central nervous system (CNS) and the cardiovascular system. The reported incidence varies depending on the study, with estimates ranging from 1 in every 1,000 nerve blocks to as high as 1 in every 1,000 nerve blocks, although this figure may be underestimated. The toxic effects of LAs may result from excessive dosing, accidental intravascular injection, or rapid systemic absorption. Clinically, LAST manifests with neurological symptoms such as perioral numbness, visual disturbances, seizures, and, in advanced stages, coma or respiratory arrest. Cardiovascular effects may include bradycardia, arrhythmias, and asystole. Risk factors fall into two categories: those that increase the plasma concentration of LAs and those that heighten patient susceptibility to their toxic effects. Key risk factors include age (infants and the elderly), comorbidities (such as renal or cardiac failure), and pregnancy, during which physiological changes increase the free fraction of the drug and neuronal sensitivity. Understanding these factors is crucial for enhancing anesthetic safety, preventing adverse events, and minimizing the morbidity and mortality associated with this complication.